Analysis of factors affecting fertility rate in modern Japan (Journal of Oriental Studies, 2017)
This article analyzes the following factors affecting birthrate in modern Japan: national-cultural factor (gender inequality in Japanese society), economic factor (increase of share of temporary workers in labor market, high cost of childrearing), social factor (increase in women’s educational attainment, increase of average age at first marriage and first birth) and psychological factor (phenomenon of «hikikomori», parasite-singles, «herbivore» men). Also a set of measures, designed to improve the reproductive behavior of Japan’s population, is proposed in the article.